Pengaruh Online Advertising, Social Media Marketing, dan Electronic Word Of Mouth Terhadap Keputusan Pembelian - Muhammad Finsa Gribaldi; Desy Prastyani (Journal of Management and Social Sciences, 2024)
Promotional efforts must be carried out using social media as a marketing tool in line with increasingly sophisticated technological advances. With promotions using social media marketing, business people must be innovative and attractive in order to influence consumer purchasing decisions. Meanwhile, promotion by means of online advertising can help potential customers understand the things they provide and help customers make purchasing decisions. Therefore, consumers who use forums or online sites to look for reviews or comments about a product often use electronic word of mouth promotions. Nowadays, cosmetics have become a special need for women to care for themselves and have good skin. This encourages women to apply cosmetics to look attractive and keep facial skin healthy. So this research aims to discuss the magnitude of the influence of online advertising, social media marketing, and electronic word of mouth on purchasing decisions. This research used a purposive sampling method involving 110 respondents who used Wardah products in the Jabodetabek area. Data analysis uses multiple linear regression. The results show that online advertising has a positive influence on purchasing decisions. Then, social media marketing has a positive influence on purchasing decisions. Then, electronic word of mouth has a positive influence on purchasing decisions. Then, online advertising, social media marketing, and electronic word of mouth simultaneously have a positive influence on purchasing decisions.